”Som om det aldri har skjedd” - Siri Hovda Ottesen; Aasfrid Tysvær (Barnboken: Tidskrift för Barnlitteraturforskning, 2022)
“As if it never happened”: Fictional Work with Forgiveness as a Value amongst 5th–7th Graders